Pengaruh Literasi Wirausaha, Literasi Digital dan Lingkungan Keluarga dalam Dunia Bisnis Digital terhadap Minat Wirausaha di Kalangan Mahasiswa Feb Ums - Andrian Maulana Ferdiyanto; Atwal Arifin (Syntax Corporation Indonesia, 2025)
This study aims to analyze the effect of entrepreneurial literacy, digital literacy, and family environment on entrepreneurial interest among students of the Faculty of Economics and Business, Universitas Muhammadiyah Surakarta (FEB UMS). In today's digital era, developing entrepreneurial interest is very important to increase the competence and independence of students as the next generation of the nation. This research uses a quantitative approach with a survey method. Data were collected through questionnaires distributed to 100 respondents of FEB UMS students selected using the slovin method. The independent variables in this study include entrepreneurial literacy (X₁), digital literacy (X₂), and family environment (X₃), while the dependent variable is entrepreneurial interest (Y). Data analysis was carried out using validity test, reliability test, classical assumption test, multiple regression analysis, as well as F test, t test, and coefficient of determination (R²).The results showed that simultaneously, entrepreneurial literacy (X1), digital literacy (X2), and family environment (X3) had a significant effect on student entrepreneurial interest. However, partially, only the family environment variable (X3) has a significant influence on student entrepreneurial interest. Meanwhile, entrepreneurial literacy (X1) and digital literacy (X2) did not show a significant effect individually. This finding indicates that support, encouragement, and parenting from the family play a major role in shaping students' entrepreneurial interest, while the level of entrepreneurial literacy and mastery of digital technology do not make a significant contribution directly.In conclusion, the family environment (X3) is the dominant factor influencing the entrepreneurial interest of FEB UMS students. The results of this study are expected to be a reference for families, educational institutions, and related parties to encourage the development of student entrepreneurial potential by providing support that is more focused on the family environment.